Synthesis of Precipitated Calcium Carbonate (PCC) as a Raw Paramagnetic Material Based on Ferrite-Calcite (Fe-CaCO3) and Its Potential Application. Issue 1 (May 2021) - Nurhayati, N; Sujiono, E H; Zharvan, V; Saleh, M; Awiseng, A T; Nursetya, M F
Abstract: Precipitated calcium carbonate (PCC) has been conducted by solid-liquid-gas route process. The PCC powder was prepared from limestone from lime powder contain dolomite as raw material and 0.5 M of glucose solution. The PCC powder then characterized using XRD to identify the phase and FTIR to identify the functional group. Further analysis shows that the PCC have one major phase CaCO3 with peak characteristic at 2θ = 29.3 ° also the FTIR spectra shows the presence of CaCO3 at 871.70 cm − and 1397.23 cm − .